The Relationship between the Role of Midwives, Maternal Knowledge and Husband Support with Compliance of Pregnant Women in HBSAG Examination at PMB Wagi Koja, North Jakarta in 2023 - Dina Arihta T; Maesaroh Maesaroh (Syntax Corporation Indonesia, 2023)
Pregnant women are a vulnerable group infected with the Hepatitis B virus. Based on World Health Organization data in 2019 it is estimated that 296 million people are infected with chronic hepatitis B with 1.5 million new infections per year. In 2019 in Indonesia, the number of pregnant women tested for hepatitis B using the HBsAg rapid diagnostic test (RDT) was 2,540,158 people (48.25%) of the target pregnant women. The purpose of this study is to determine the relationship between the role of midwives, maternal knowledge, husband support and compliance of pregnant women in conducting HBsAg examinations at PMB Wagi Koja, North Jakarta in 2023. This research method uses an observational survey and is a type of quantitative research, with a cross-sectional study design. The number of samples in this study was 32 people, with the sampling technique being Total side. The results in this study are P value < α, where Ha is accepted and H0 is rejected, so it can be concluded that there is a relationship between the role of midwives (P value = 0.036 and OR=6,500), knowledge (P value = 0.015 and OR=8,750) and husband support (P value = 0.029 and OR=7,333) with the compliance of pregnant women in conducting HBsAg examinations at PMB Wagi Koja, North Jakarta in 2023. The conclusion in this study is that there is a relationship between the role of midwives, knowledge and support of husbands with the compliance of pregnant women in conducting HBsAg examinations at PMB Wagi Koja, North Jakarta in 2023. PMB Koja is expected to provide counseling and education on the importance of pregnancy checks, especially HBsAg examinations and advise husbands and families to provide emotional and instrumental support and facilitate mothers' needs during the examination.